1985
DOI: 10.1177/001698628502900409
|View full text |Cite
|
Sign up to set email alerts
|

How Did Six Highly Accelerated Gifted Students Fare in Graduate School?

Abstract: This article reports follow-up information on six very young college graduates. The myth of "early ripe, early rot" is clearly refuted by the outstanding success of each of these six young accelerants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…These early entrants were followed up and were found to be highly successful in college and afterwards. Subsequently, other cohorts of young college students were studied, leading to a general conclusion that groups of early college entrants fare well academically without having social and emotional problems (see, for example, Stanley, 1985;Brody et al, 1988Brody & Stanley, 1991).…”
Section: Accelerationmentioning
confidence: 99%
“…These early entrants were followed up and were found to be highly successful in college and afterwards. Subsequently, other cohorts of young college students were studied, leading to a general conclusion that groups of early college entrants fare well academically without having social and emotional problems (see, for example, Stanley, 1985;Brody et al, 1988Brody & Stanley, 1991).…”
Section: Accelerationmentioning
confidence: 99%
“…The Study of Mathematically Precocious Youth (SMPY) and similar talent search programs have a long history of studying the longitudinal effects of acceleration among highly talented students (Barnett & Durden, 1993; Benbow, Lubinski, Shea, & Eftekhari-Sanjani, 2000; Brody et al, 1990; Kolitch & Brody, 1992; Lubinski & Benbow, 2006; Lubinski, Webb, Morelock, & Benbow, 2001; Richardson & Benbow, 1990; Stanley, 1973, 1985, 1988; Stanley & McGill, 1986; Swiatek, 2002; Swiatek & Benbow, 1991a, 1991b, 1992). This rich collection of data indicates that early attempts at acceleration were successful (e.g., Stanley, 1973), and the history of Talent Searches has continued to show academic benefits of acceleration (e.g., Stanley, 1988; Swiatek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the widespread resistance to early entrance, further research that highlights the social and emotional adjustment of these students is needed so that parents and prospective early entrants will base their decisions on evidence, rather than myths. Additionally, since research on early entrants has largely focused on long-term outcomes and has demonstrated their educational and occupational success over time (Stanley, 1985a(Stanley, , 1985bStanley & Benbow, 1983;Stanley & McGill, 1986), more empirical attention needs to be directed at the short-term impact of entering college early. For example, it would be useful to learn more about how early entrants adjust during their first semester in college, which may arguably be the most critical juncture for them in terms oftheir adjustment.…”
mentioning
confidence: 99%